New early Aptian rudists (Bivalvia-Hippuritacea) from the Huetamo area in southwestem Mexico - Gloria Alencáster; Jerjes Pantoja-Alor (Revista Mexicana de Ciencias Geológicas)
The new taxa of caprinid rudists Pantojaloria shaerica and Caprina massei are described. They are derived from a thick sequence of carbonate sediments recurrently interlayered with volcanic rocks,… in order to continue, download the full paper in PDF.